Perspektif Pajak Atas Pengaruh Aset Pajak Tangguhan dan Ukuran Perusahaan Terhadap Manajemen Laba (Perusahaan Listing Manufaktur 2018-2020) - Muhammad Faisal Akbar Ibrahimy; Gunadi Gunadi (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
For the last decade, there has been many cases of earning management on Indonesia. This follow suits with the agency theory as management is trying to achieve their own personal goal. Management will try to manipulate the information on financial report thus doing earning management. Some of the widely used indicators to detect earning management are deferred tax asset and firm size. Firm size will be represented by total asset of the company. Deferred tax asset will be represented by asset depreciation. The purpose of this study is to examine the effect of Deferred tax asset and firm size on earning management. The result of this research will be studied deeper using interview technique. The research data show that both hypothesis are accepted. The statistic has determined that there are positive relation between deferred tax asset and firm size to earning management. Management used the depreciation method to increase profit or lower the tax obligation on that period. The bigger the firm means that there are bigger chances of earning management.